The Unique Bioorthogonal Chemistry of Isonitriles - Deb, Titas; Franzini, Raphael M. (Synlett, 2020)
The isocyano group is the structurally most compact bioorthogonal group known. It reacts with tetrazines under physiological conditions and has great potential for widespread use in the biosciences. In this account, we highlight the unique properties of the isocyano group as a bioorthogonal functionality. Protecting group chemistry based on the reaction of isonitriles and tetrazines that allows releasing payloads is a particular focus of the article. We further discuss the atypical steric attractions that take place in the transition state of the reaction between isonitriles and tetrazines, which result in an increase in the rate of the reaction with steric bulk of the tetrazine substituents. These findings will open up new possibilities in bioorthogonal chemistry where reactivity and stability are simultaneously desired.1 Introduction2 The Isocyano Group: A Structurally Compact Group for Bioorthogonal Chemistry3 Bioorthogonal Protecting Group Chemistry4 Steric Attractions in the Transition State Accelerate the Cycloaddition of Isonitriles and Tetrazines5 Reactions of Tetrazines and Isonitriles are Compatible with Biomolecules and Living Organisms6 Conclusions
Keywords: bioorthogonal chemistry; isocyanides; protecting groups; steric attraction; cycloadditions